2021
DOI: 10.1155/2021/6652099
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Mechanism of Tuina Promoting the Recovery of Peripheral Nerve Injury

Abstract: Tuina, as one of the characteristic external therapies of Traditional Chinese Medicine (TCM), has been used to treat the disease caused by peripheral nerve injury (PNI) for thousands of years. An increasing number of clinical trials and animal experiments have demonstrated that tuina can improve the symptoms and promote the recovery of damaged nerves. This review focuses on the mechanistic studies of tuina in promoting the recovery of PNI, which might provide a neurobiological foundation for the effects of tui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Reports have suggested that Tuina would improve functional outcomes following peripheral nerve injury repair (Z. Liu et al, 2021;. However, it is not well understood whether the long-lasting cortical plasticity is involved in the improvement of function after Tuina therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have suggested that Tuina would improve functional outcomes following peripheral nerve injury repair (Z. Liu et al, 2021;. However, it is not well understood whether the long-lasting cortical plasticity is involved in the improvement of function after Tuina therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As more studies regarding to Tuina therapy in the treatment of peripheral nerve injury have been reported, investigations on brain plasticity have become essential for a better understanding of its effects and appropriate application in clinical practice (Z. Liu et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids are the lipids containing phosphorus, mainly including phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS), and phosphatidic acid (PA) . Phospholipids are the basic components of cell membranes, nuclear membranes, and lipid membranes in animal or plant cells, as well as one of the components of nerve cells. , They can protect nerve cells, accelerate the transmission of biomedical information, and repair the damaged brain. , Due to the presence of both hydrophilic and lipophilic groups, phospholipids can be used to encapsulate, transport and sustainably release water-soluble, oil-soluble, and amphiphilic substances . For example, by combining polyphenols with phospholipids under certain conditions, a polyphenol–phospholipid complex can be obtained, which not only changes the physicochemical properties of polyphenols but also masks their unpleasant flavor and enhances their stability. , In recent years, such phospholipid complexes have been widely applied in many fields such as food, medicine, and cosmetics …”
Section: Introductionmentioning
confidence: 99%
“…The goal of these maneuvers is to reduce pain while also having a direct impact on the underlying disease process. Tuina has been shown to be effective for many clinical conditions, such as cervical vertigo, [7] hypertension, [8] chronic fatigue syndrome, [9] chronic neck pain, [10] peripheral nerve injury, [11,12] headache, [13] and various musculoskeletal conditions. [14] It has also become an important treatment method for LBP.…”
Section: Introductionmentioning
confidence: 99%